Endometrial scratching for women with previous IVF failure undergoing IVF treatment. (April 2015) - Gibreel, Ahmed; El-Adawi, Noha; Elgindy, Eman; Al-Inany, Hesham; Allakany, Nasser; Tournaye, Herman
Abstract The purpose of this study was to find out whether endometrial scratching could improve live birth rate in women with previous IVF failure undergoing fresh IVF cycle. In a randomized controlled trial, 387women with previous IVF failure were divided into two groups. Group A (193 women) was subjected to endometrial biopsy procedure twice. Group B (194 women) was subjected to a placebo procedure. Our results showed no difference in live birth rate between the two groups of women (47.2% versus 38.1%, p = 0.08). However, regression analysis revealed that endometrial scratching was an independent predictor of live birth in the subgroup of women with two or more previous failure after control of other independent predictors (odds ratio (OR) 3.4, p = 0.005). We conclude that endometrial scratching does not improve live birth rate in women undergoing IVF treatment with previous one IVF failure. Nevertheless, it may improve live birth in women with two or more previous IVF failures.